Co-Creativity Assessment in the Process of Game Creation - Romero, Margarida; Sylvester, Arnab; Cindy, De Smet; Fitri Suraya, Mohamad; Sarra, Abdelouma; Jacey Lynn, Minoi; Luca, Morini (2018)
We consider game design as a sociocultural and knowledge modelling activity, engaging the participation in the design of a scenario and a game universe based on a real or imaginary socio-historical context, where characters can introduce life narratives and interaction that display either known social realities or entirely new ones. In this research, participants of the co-creation activity are Malaysian students who are working in groups to design educational games for rural school children. After the co-creativity activity, learners were invited to answer the co-creativity scale, an adapted version of the Assessment Scale of Creative Collaboration (ASCC), combining both the co-creativity factors and learners’ experiences on their interests, and the difficulties during the cocreativity process. The preliminary results showed a high diversity on the participants’ attitudes towards collaboration, especially related to their preferences towards individual or collaborative work.